Reduction in ammonium ions in sludge liquor / Vienas iš būdų mažinti amonio jonų koncentraciją dumblo vandenyje - Eglė Šlajūtė; Aušra Mažeikienė (Mokslas: Lietuvos Ateitis, 2013)
Liquor rejected from the centrifugation of the digested sludge can contain the concentrations of ammonium ions up to 1750 mg/L. These loads are usually returned to the intake of wastewater treatment plants (WWTP) without additional treatment and can have a negative impact on biological wastewater and/or sludge treatment processes, e.g. phosphorus and nitrogen removal. This article deals with the use of naturally obtained sorbent, zeolite, in batch and column test procedure for removing ammonium from the rejected liquor. This research study was carried out using different sizes of zeolite particles: 0.8–1.6 mm and 1.6–2.5 mm. The highest efficiency of ammonium removal (up to 98 %) was achieved by applying the zeolite particles of 0.8–1.6 mm.